HUBUNGAN KEMAMPUAN KERJA DAN DISIPLIN KERJA DENGAN KINERJA PEGAWAI DI BADAN PELAYANAN PERIJINAN TERPADU KOTA SEMARANG - Aurelia Maretha Dwi Arini; Margareta Suryaningsih; Titik Djumiarti (Journal of Public Policy and Management Review, 2014)
This study aims to assess the employee's performance Integrated Licensing Service Agency of Semarang with the ability to work and work discipline. The problems that exist in this study is still less than optimal employee performance seen from the lack of ability to work and work discipline. This study was conducted to determine how much the relationship between work ability variables (X1) and work discipline (X2) with employee performance (Y). In this study the method used is explanatory, that is the type of research that is used to examine the relationship between the variables studied. The data obtained by questionnaires given to 41 employees as respondents in the Integrated Licensing Service Agency of Semarang.The results of this study indicate that the hypothesis that there is a positive relationship between the variables work ability and work discipline to employee performance Integrated Licensing Service Agency of Semarang acceptable significantly by 82.44% coefficient of determination means the employee's performance changes by 82.44% as a result influence of ability to work and work discipline. While the remaining 17.56% is influenced by other factors such as motivation, leadership and work environment.The results showed a positive and significant relationship between the variables work ability and work discipline on employee performance. This means that in order to improve employee performance Integrated Licensing Service Agency of Semarang can be done by increasing the employability and self-discipline by giving an understanding of the work presented, provide training to employees, adherence to clock in and leave work and sincerity in completing work responsibilty.